Análise da fauna silvestre recebida no Zoobotânico Municipal de São José do Rio Preto/SP, no período de 2O2O a 2023 - Costa, Lidiane de Almeida (Universidade Federal de São Carlos, 2025)
The relationship between humans and wildlife has been profoundly affected by anthropogenic activities such as deforestation, fires, trafficking, roadkill, and mistreatment. In this context, institutions such as the Environmental Police, Wildlife Screening Centers (CETAS), and zoos play a crucial role in the rescue, rehabilitation, and disposition of animals. The Municipal Zoobotanical Park of São José do Rio Preto, founded in 1973, stands out regionally for receiving and treating animals affected by these pressures. This study evaluated the wild animals received by the institution between 2020 and 2023, characterizing their taxonomic composition, intake categories, species occurrence frequency, origin, developmental stage, and conservation status, in addition to comparing the findings with the scientific literature. Data were obtained from the “Quadro PMA” database (Environmental Military Police) of the Rio Preto Zoobotanical, which gathers information on identification, provenance, rescue history, treatment, and final disposition. During the analyzed period, 4,623 individuals were recorded. The most representative categories were “healthy,” “orphaned,” and “roadkill.”. Birds constituted the predominant class in most occurrences. Among the findings, parakeets (Psittacidae) and opossums (Didelphidae) were among the most frequent. The municipality of São José do Rio Preto accounted for the highest number of records in most categories. Although many species were classified as “Least Concern” (LC), vulnerable or near-threatened species were also recorded, such as the giant anteater (VU), the red-footed tortoise (VU), and the turquoise-fronted parrot (NT). Highway BR-153 stood out as a potential factor associated with the high incidence of roadkill and cases related to trafficking. The observed patterns converge with studies conducted in other regions of Brazil, highlighting the impact of human activities on wildlife and reinforcing the importance of institutions responsible for sheltering, management, and conservation. The data also underscore the relevance of São José do Rio Preto as a receiving hub and the influence of regional factors, such as BR-153, on the dynamics of occurrences.
Analysis of the wild fauna received at the Municipal Zoobotanical of São José do Rio Preto/SP, from 2O2O to 2023
Keywords: Histórico; Espécies ameaçadas; Conservação; History; Threatened species; Conservation; CIENCIAS BIOLOGICAS::ZOOLOGIA; 15. Vida Terrestre